Implementasi Merdeka Belajar Dalam Pembelajaran Anak Usia Dini Berlandaskan Tri Kaya Parisudha - I Made Ardika Yasa; Ida Bagus Alit Arta Wiguna (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2022)
Community service is one part of the tri dharma of higher education that must be carried out by a lecturer, community service this time has the theme of Development of Independent Learning as a Media for Realizing Early Childhood Learning Based on Tri Kaya Parisudha which is carried out by the Study Program Community Service Team S1 PG-PAUD at Teratai PAUD, Prince Sangupati Foundation, Leneng Village, Praya District, Central Lombok Regency with an implementation time of 5 (five) days from 18, 19, 20, 21 and 22 September 2021, through sradha bhakti coaching activities with Dharmagita, coaching Traditional Balinese dances, coaching learning strategies, coaching yoga, coaching spiritual songs with Hindu nuances, coaching memorizing mantra verse, coaching creative/modern dances, coaching health protocols and a clean and healthy lifestyle. All of the activities carried out involve the community, especially early childhood students, parents, adn young Hindus who live in the Leneng village area so later it can be expected that a synergistic relationship will occur between the community and the Gde Pudja Mataram State Hindu Institute for the realization of the Vision and Mission of the institution in general.